Marker less augmented reality with compass assistance / Muhammad Asyraf Mohammad - Mohammad, Muhammad Asyraf (2011)
This paper is about implementing augmented reality on android mobile phone. This augmented reality will be a marker less base. The allocation for the object will be base on compass direction that includes the degrees of azimuth and inclination. This compass controlled by accelerometer of the device.